Effects of warming-up on physical performance: a systematic review with meta-analysis - Fradkin, A. J.; Zazryn, T. R.; Smoliga, J. M. (The Journal of Strength and Conditioning Research, 2010)
The value of warming-up is a worthy research problem because it is not known whether warming-up benefits, harms, or has no effect on individuals. The purpose of this study was to review the evidence relating to performance improvement using a warm-up. A systematic review and meta-analysis were undertaken. Relevant studies were identified by searching Medline, SPORTDiscus, and PubMed (1966-April 2008). Studies investigating the effects of warming-up on performance improvement in physical activities were included. Studies were included only if the subjects were human and only if the warm-up included activities other than stretching. The quality of included studies was assessed independently by 2 assessors using the Physiotherapy Evidence Database scale. Thirty-two studies, all of high quality (6.5-9 [mean = 7.6] of 10) reported sufficient data (quality score >6) on the effects of warming-up on performance improvement. Warm-up was shown to improve performance in 79% of the criterions examined. This analysis has shown that performance improvements can be demonstrated after completion of adequate warm-up activities, and there is little evidence to suggest that warming-up is detrimental to sports participants. Because there were few well-conducted, randomized, controlled trials undertaken, more of these are needed to further determine the role of warming-up in relation to performance improvement.